2017
DOI: 10.1002/pri.1690
|View full text |Cite
|
Sign up to set email alerts
|

Assisted autogenic drainage in infants and young children hospitalized with uncomplicated pneumonia, a pilot study

Abstract: Background and purpose: Pneumonia is the most important respiratory problem in low-to-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…In addition to clinical outcomes, cost prevention and high demands for hospital beds in lower-resourced countries could be contributing factors for short duration of hospital stay (Argent et al 2014:7-14). However, three randomised controlled trials on children hospitalised with pneumonia reported a median duration of hospital stay of six to eight days (Corten et al 2018Lukrafka et al 2012:967-971;Paludo et al 2008:791-794), which is similar to the duration of hospitalisation for pneumonia in our study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition to clinical outcomes, cost prevention and high demands for hospital beds in lower-resourced countries could be contributing factors for short duration of hospital stay (Argent et al 2014:7-14). However, three randomised controlled trials on children hospitalised with pneumonia reported a median duration of hospital stay of six to eight days (Corten et al 2018Lukrafka et al 2012:967-971;Paludo et al 2008:791-794), which is similar to the duration of hospitalisation for pneumonia in our study.…”
Section: Discussionsupporting
confidence: 84%
“…However, the RCT by Lukrafka et al also reported a median 2 days longer hospital stay in children who received ACT, compared to controls, which was not statistically significant, possibly owing to insufficient sample size (Lukrafka et al 2012:967-971). Other studies have not reported significant differences for length of stay when receiving ACT in children hospitalised with pneumonia (Corten et al 2018Paludo et al 2008:791-794). Prospective studies are recommended to confirm these results and to determine causality.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Assisted autogenic drainage may be performed with the infant on the physiotherapists’ lap, bouncing on a therapy ball, which may encourage relaxation of the child and improve expiratory airflow (Lee, Button & Tannenbaum 2017:2). A pilot randomised controlled trial ( n = 29) (Corten et al 2018) to determine the effect of assisted autogenic drainage in young children admitted to hospital with uncomplicated pneumonia, compared to standard nursing care alone (Corten et al 2018), reported there was a trend towards a shorter time to discharge in the intervention group ( p = 0.06), but no other significant benefit of assisted autogenic drainage. Importantly, though, no adverse events occurred, suggesting that this technique could be added to our ‘ACT toolbox’ for use in infants and children, and this warrants further investigation (Corten et al 2018).…”
Section: Airway Clearance Techniquesmentioning
confidence: 99%
“…Therapy is performed on the parent’s knee with 2 min alternating cycles of PEP and AAD (four times). 5 The initial PEP resistor diameter is set to 3.5 mm for term babies. This has been determined through clinical experience; to achieve an increase in resistance without a significant increase in work of breathing.…”
mentioning
confidence: 99%